Democratization - Haerpfer, Christian W. (Oxford University Press, 2009)
Klappentext: Democratization is the first textbook to focus on the "global wave of democratization" that has been occurring since around 1970. Bringing together leading authors from diverse international backgrounds, it introduces students to the theoretical and practical dimensions of the subject in an authoritative, accessible, and systematic way. The book takes into account the international factors that affect politics at the level of the nation state, showing students the direction in which the discipline is moving. It is accompanied by an innovative companion website that provides numerous resources for students and instructors. Democratization covers several key themes including: * Theories of democratization and their relation to democratic theory * Critical prerequisites and driving social forces of democratic transition * Pivotal actors and institutions involved in democratization * Conditions for democratic survival, the consolidation of newly democratized countries, and the analysis of failed democratization * Demonstrations of how these factors have played a role in the different regions in which the global wave of democratization has transplaced authoritarian and communist systems * Possible futures of democratization worldwide.